Moja gwiazda - Nowak, Felicja (Bialystok : Zaklady Wydawnicze "Versus", 1991)
A Jewish woman from Poland writes about her experiences under the Nazi occupation and how she was helped by her countrymen to escape from a concentration camp-bound train.
Keywords: World War, 1939-1945 -- Jews -- Poland -- Bialystok; Holocaust, Jewish (1939-1945) -- Poland -- Bialystok -- Personal narratives; Jews -- Poland -- Warsaw; Jews -- Poland -- Bialystok